Agrobacterium-mediated Genetic Transformation of Local Cultivars of Chickpea (Cicer arietinum L.) - Sharmin, Ripa Akter; Akter, Jasmin; Sarker, R. H.; Hoque, M. I. (Plant Tissue Culture and Biotechnology, 2012)
Agrobacterium-mediated genetic transformation protocol was established for two chickpea (Cicer arietinum L.) varieties, namely Barichhola-4 (Bch-4) and Barichhola-5 (Bch-5). Transformation ability of different explants such as decapitated embryo with single cotyledon disc (DEC), decapitated embryo (DE) and slice embryo decapitated at shoot end with single cotyledon disc (SEC) were tested using Agrobacterium tumefaciens strain LBA4404 harbouring binary plasmid pBI121, containing the GUS and nptII genes. Maximum transformation ability was exhibited by explants of decapitated embryo (DE) from Barichhola-5 (Bch-5). The optimum regeneration from the transformed tissue was achieved on MS supplemented with 0.5 mg/l BAP, 0.5 mg/l Kn and 0.2 mg/l NAA along with double the amount of CaCl2 and KNO3. Selection of the transformed shoots was carried out by gradually increasing the concentration of kanamycin to 150 mg/l. Stable expression of the GUS gene was detected in various parts of the transformed shoots through GUS histochemical assay. Stable integration of nptII gene within the genomic DNA from these transformed shoots was confirmed through PCR analysis. DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11258 Plant Tissue Cult. & Biotech. 22(1): 41-50, 2012 (June)